Synthesis and evaluation of novel thiosemicarbazone and semicarbazone analogs with both anti-proliferative and anti-metastatic activities against triple negative breast cancer. (1st May 2021) - Bai, Chengfeng; Wu, Shuangjie; Ren, Shengnan; Zhu, Meiqi; Luo, Guoshun; Xiang, Hua
Graphical abstract: Highlights: Hecogenin thiosemicarbazone and semicarbazone hybrids are helpful for design of triple-negative breast cancer agents. 4c possesses significant antiproliferative activity against breast cancer (MCF-7 and MDA-MB-231 cells), lung cancer cells (A549) and colon cancer cells (HT-29). 4c could induce MDA-MB-231 cells apoptosis and arrest cell cycle in Sub-G1 phase. 4c display potent anti-migration and anti-invasion activity. Abstract: Triple-negative breast cancer (TNBC) is one of the most aggressive cancer with high mortality and recurrence rates. Hecogenin, a steroidal sapogenin, is reported as a potential anti-tumor agent against breast cancer. However, the moderate activity limits its further application in clinical. With the aim to identify novel analogues that are especially efficacious in therapy of TNBC, a series of novel hecogenin thiosemicarbazone and semicarbazone derivatives were designed, synthesized and biologically evaluated. Screening of cytotoxicity revealed that 4c could potently inhibit the proliferation of breast cancer cells (MCF-7 and MDA-MB-231 cells), lung cancer cells (A549) and colon cancer cells (HT-29) at low μM level. Importantly, further mechanism studies indicated the ability of 4c in inducing apoptosis of MDA-MB-231 cells by arresting the cell cycle. Moreover, 4c notably suppressed the migration and invasion of MDA-MB-231 cells compared to its parent hecogenin at the equal concentration.